P. falciparum and P. vivax Orthologous Coiled-Coil Candidates for a Potential Cross-Protective Vaccine - Ayadi, Imen; Balam, Saidou; Audran, Régine; Bikorimana, Jean-Pierre; Nebie, Issa; Diakité, Mahamadou; Felger, Ingrid; Tanner, Marcel; Spertini, François; Corradin, Giampietro; Arevalo, Myriam; Herrera, Socrates; et al. (Frontiers in Immunology, 2020)
During the last four decades, significant efforts have been invested to develop vaccines against malaria. Although most efforts are focused on the development of P. falciparum vaccines, the current availability of the parasite genomes, bioinformatics tools, and both high throughput systems for recombinant and synthetic antigen production permit to accelerate vaccine development against P. vivax parasite. We have previously in silico identified several P. falciparum and P. vivax proteins containing α-helical coiled-coil motifs that represent novel putative antigens for vaccine development since they are highly immunogenic and have been associated to protection in many in vitro functional assays. Here, we selected five pairs of P. falciparum and P. vivax orthologous peptides to assess their sero-reactivity to plasma samples collected in African P. falciparum endemic countries. Pf-Pv cross-reactivity was also investigated. The pairs Pf27/Pv27, Pf43/Pv43, and Pf45/Pv45 resulted to be the most promising candidates for a cross-protective vaccine because they showed a high degree of recognition in direct and competition ELISA assays and good cross-reactivity with their respective orthologue. The recognition of P. vivax peptides by plasma of P. falciparum infected people indicates the existence of high degree of cross-reactivity between these two Plasmodium species and, therefore, suggests the design of longer polypeptides combining these epitopes to assess their immunogenicity and protective efficacy in animal models.